The “Non-Treated” Versus “LT3-Treated” Protocols of Short-Term Hypothyroidism Induction in Differentiated Thyroid Cancer: An Analysis of Hypothyroid Complications, Mood Disorders, and Quality of Life - Tufekci, Damla; Ayaz, Teslime; Sahin, Serap Baydur; Hocaoglu, Cicek (Hormone and Metabolic Research, 2023)
This study aimed to compare “non-treated” versus “levotriiodothyronine (LT3)-treated” protocols of short-term hypothyroidism induction prior to radioactive iodine (RAI) ablation therapy in differentiated thyroid cancer (DTC). A total of 120 DTC patients who had thyroxine withdrawal either via 4-week hypothyroidism induction (non-treated group, n=60) or 2-week administration and then 2-week withdrawal of LT3 (LT3-treated group, n=60) to induce hypothyroid state prior to RAI ablation after initial surgery were included. Complications related to hypothyroidism-induction, Beck Depression Inventory (BDI), Hospital Anxiety-Depression Scale (HADS), and SF-36 health-related quality of life (HRQoL) scores were recorded. In the non-treated group, transition from euthyroid to hypothyroid state was associated with significant increase in the likelihood of moderate-to-severe depression on BDI (p<0.001), presence of depression on HADS-D (p<0.001), presence of anxiety on HADS-A (6.7% during euthyroid state vs. 33.3% during hypothyroid state, p<0.001), and major syndrome on BPRS (0.0 vs. 10.0%, p=0.001) as well as significant decrease in all SF-36 HRQoL domain scores (p<0.001 for each). In conclusion, our findings indicate the likelihood of L3-treatment to enable a more favorable transition period from euthyroid to hypothyroid state without experiencing a deterioration in depression, anxiety, or HRQoL.
Keywords: differentiated thyroid carcinoma; hypothyroidism induction; LT3- protocol; depression; anxiety; quality of life